PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR PADA KUALITAS AUDIT DIMODERASI OLEH TEKANAN KLIEN - Dewi, Dewa Ayu Candra; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 11 No 1 (2015), 2015)
This study aims to determine the effect of the competence and independence of the auditors on audit quality by clients as a moderating variable pressure. This study took place throughout the public accounting firms in Bali. Where sampling technique using purposive sampling with criteria auditors who have worked for 1 year. The data used in this study are the primary data questionnaire. The results of this study indicate that competence has no significant effect on audit quality. Then the hypothesis that the two variables auditor competence and client pressure to weaken the relationship auditor competence and client pressure on audit quality variable indicates the second hypothesis is accepted. The third hypothesis of independence affect the independence of the higher audit quality possessed by an auditor, the audit quality produced is also getting better. And the results of the hypothesis that four variables auditor independence and client pressure has no significant effect on audit quality that hypothesis 4 is rejected.
Keywords: competence, independence, client pressure, the quality of the audit